Persuasive Papers, Speeches, and Campaigns - Laura Gorham; Ricky Telg; Tracy Irani (EDIS)
Persuasion can be used in written essays, speeches or as part of media campaigns that attempt to influence an audience to change their thinking or behavior. This publication will familiarize you with the tools necessary to develop a persuasive essay, speech, or media campaign. This 3-page fact sheet was written by Laura Gorham, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, July 2013.